Knowledge Battlegrounds: Navigating Security Imperatives in Global Academia - Maldonado-Maldonado, Alma (International Higher Education, 2025)
<h3 id="this-paper-explores-the-interplay-between-academia-and-geopolitics-revealing-how-universities-have-become-battlegrounds-for-national-security-interests-the-paper-unveils-four-dimensions-security-driven-internationalization-constraints-the-allure-of-global-talent-mobility-the-digital-espionage-in-academic-settings-and-the-politicization-of-knowledge-in-a-world-of-intensifying-rivalries-the-article-presents-urgent-questions-about-preserving-academic-freedom-amid-competing-national-desires-in-a-context-where-higher-education-is-crucial-for-development-and-innovation" data-pm-slice="1 1 []">This paper explores the interplay between academia and geopolitics, revealing how universities have become battlegrounds for national security interests. The paper unveils four dimensions: security-driven internationalization constraints, the allure of global talent mobility, the digital espionage in academic settings, and the politicization of knowledge. In a world of intensifying rivalries, the article presents urgent questions about preserving academic freedom amid competing national desires in a context where higher education is crucial for development and innovation.